Analysis of the Impact of Digital Competency Training, Job Happiness, and Employee Productivity on Turnover Rates in the Indonesian E-Commerce Industry - Nanny Mayasari; Ade Suhara; Devi Marlita; Ria Estiana; Rinny Dharma Diani (West Science Interdisciplinary Studies, 2024)
This quantitative study investigates the relationships between digital competency training, job happiness, employee productivity, and turnover rates in the Indonesian e-commerce industry. Data were collected from 128 employees working in various e-commerce companies through structured questionnaires. Structural equation modeling (SEM) analysis was employed to analyze the data. Theresults reveal significant positive relationships between digital competency training and both job happiness and employee productivity. Furthermore, job happiness and employee productivity exhibit significant negative associations with turnover intentions. These findings highlight the importance of investing in digital skills development, fostering a positive work environment, and promoting employee productivity to reduce turnover rates in the e-commerce industry. Theoretical and practical implications are discussed, along with suggestions for future research.